PENGARUH PERJANJIAN PERDAGANGAN INTERNASIONAL TERHADAP KEBIJAKAN PERLINDUNGAN DATA PRIBADI - Widjaja, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The influence of international trade agreements on personal data protection policies is a topic that examines how international standards and frameworks influence domestic regulations related to data privacy. International trade agreements, such as GATT and various free trade agreements, require member countries to implement regulations that support the security and transfer of cross-border data. Challenges arise when countries have to adjust their personal data protection policies to international obligations, which can lead to potential conflicts between national interests and international compliance. Nevertheless, this agreement has a positive impact by encouraging the harmonisation of global data protection standards, reducing trade barriers, and improving the security of personal data. The successful implementation of this policy depends heavily on the commitment and cooperation between countries in implementing effective regulations that are in line with global needs.